2017
DOI: 10.1016/j.sleep.2016.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Early features associated with the neurocognitive development at 36 months of age: the AuBE study

Abstract: We showed that early features including infant sleep characteristics influence IQ scores at 36 months old. Some of these may be accessible to prevention.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
3
5
0
Order By: Relevance
“…Also, we performed longitudinal analyses of the associations between TV exposure in early childhood and later verbal IQ at age 5–6 years, a method ensuring that a potential cause precedes its potential effect, unlike cross-sectional analyses that have been the most frequent in the literature so far. Finally, we performed a sensitivity analysis with factors identified as potential mediators between TV exposure and language development: the results remained unchanged when including sleep characteristics, which agrees with recent results identifying a main action of sleep quality and quantity on executive functions rather than language development 42 .…”
Section: Discussionsupporting
confidence: 85%
“…Also, we performed longitudinal analyses of the associations between TV exposure in early childhood and later verbal IQ at age 5–6 years, a method ensuring that a potential cause precedes its potential effect, unlike cross-sectional analyses that have been the most frequent in the literature so far. Finally, we performed a sensitivity analysis with factors identified as potential mediators between TV exposure and language development: the results remained unchanged when including sleep characteristics, which agrees with recent results identifying a main action of sleep quality and quantity on executive functions rather than language development 42 .…”
Section: Discussionsupporting
confidence: 85%
“…We report for the first time an association between night sleep fragmentation, objectively measured by polysomnography in the early months of life and lower verbal performance scores at 36 months of age. These results are in agreement with other studies that used objective sleep evaluation such as actigraphy [6,7], but also with a previous study that we reported which used parental night awakening reports at 6 months [11]. Other authors reported that fragmented sleep has been associated with memory difficulties and poorer academic achievement in older children [18] probably due to lower sleep efficiency tracking throughout childhood [19].…”
Section: Night Sleep Fragmentation and Neurocognitive Development At supporting
confidence: 92%
“…showed that snore-related arousals in the absence of apneas or hypopneas, are negatively correlated with mental scores [34]. In the previous study that we reported, frequent snoring signaled by parents at 18 months was associated with lower PIQ and Block design scores at 3 years of age [11].…”
Section: Night Sleep Fragmentation and Neurocognitive Development At supporting
confidence: 45%
See 1 more Smart Citation
“…However, day sleep in early childhood is less investigated in relation to cognitive performance. Plancoulaine et al found that day/night sleep ratio was positively associated with Full Scale IQ scores [ 44 ] Knowland et al also showed that more night sleep relative to day sleep, was predictive of better receptive vocabulary [ 45 ]. Napping has been associated with shorter night sleep and poorer sleep quality [ 41 ] and increased napping has been previously reported to negatively affect language comprehension [ 46 ].…”
Section: Discussionmentioning
confidence: 99%